A REVIEW ON MODELS OF INFORMATION AND COMMUNICATIONS TECHNOLOGY (ICT): RETHINKING THE ONLINE TEACHING IN HIGHER EDUCATION CONTEXT (Journal of Foreign Language Studies, 2020)
A change from traditional modality of teaching delivery to online teaching and learning has put high pressure on higher education institutions who are struggling in seeking suitable models for ICT integration so as to achieve both curriculum agenda and the quality assurance of higher order thinking. To this end, this article aims to offer critical insights into five ICT models widely used in the world education, being applicable to online delivery in higher education in Vietnam, mainly: UTAUT, SAMR, TPACK, R2D2 and RAT. These models are reviewed from three fundamental perspectives: strengths, weaknesses, and effectiveness in their application in higher education in Vietnam. The paper also highlights open suggestions for best practices of online teaching/learning as well as recommendations for effective use of these models in Vietnamese educational institutions.
Keywords: higher education; ICT; model; online teaching; effective